Amplifier front-end design in dry-electrode electrocardiography - Assambo, Cédric E. (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2011)
This thesis presents an analytical approach to some key issues related to the design of biopotential amplifiers for use in long-term ambulatory recording of the electrocardiogram (ECG) employing pasteless or dry electrodes. The two principal problems of low-frequency distortion and immunity to common-mode interfering signals are analysed in detail. There is also an algorithm for the identification of the model parameters of a group of systems simulated as a double-time-constant network in an attempt to characterise the interface composed of the skin and the sensing electrodes. In the case of low-frequency distortion, new input impedance specifications for dry-electrode electrocardiography are derived from the analysis of performance requirements issued in international standards and recommendations. This is necessary if the low-frequency components in the ECG that contain valuable clinical information about the condition of the cardiovascular system are to be faithfully reproduced. The factors defining the ability of the recording system to effectively reject external unwanted voltages are then determined to allow the suitability of a small number of amplifier circuit configurations to be assessed. The design of new instrumentation amplifiers is finally outlined and their performance evaluated in a worst-case scenario.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.